2014
DOI: 10.1111/1747-0080.12114
|View full text |Cite
|
Sign up to set email alerts
|

Systems‐practice framework: An integrated approach for foodservice management

Abstract: Aim There is increasing pressure on foodservice organisations to improve the sustainability of their operations and to do so practitioners must be equipped with appropriate tools. In this paper, a tool to guide management strategies for pro‐environmental behaviour change is introduced. The tool is based on a new framework that combines two existing models: the widely used foodservice ‘systems model’ and a model from sociology proven to be effective for understanding sustainable practices, the ‘social practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Managers could motivate staff by finding a common positive perspective to initiate changes. Goonan et al suggest a framework combination of the commonly used ‘systems model’ and ‘social practice model’ as a tool to introduce sustainable practices in a foodservice . This combination approach may also be useful for introducing environmental education into university foodservice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Managers could motivate staff by finding a common positive perspective to initiate changes. Goonan et al suggest a framework combination of the commonly used ‘systems model’ and ‘social practice model’ as a tool to introduce sustainable practices in a foodservice . This combination approach may also be useful for introducing environmental education into university foodservice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Skeptics were the minority group, there is a chance this factor might be represented in some foodservices. To overcome these obstacles, the framework by Goonan et al . could show Skeptics that financial accountability, hygiene and customer service outcomes can still be withheld.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this framework, the system is an open system which impacts and is impacted upon, by its environment (Gregiore, 1913). A search of literature of research on foodservice management systems revealed very few articles, however a very recent article combined the systems framework with the social practice model with ethnography (Goonan, Mirosa, Spence 2015). So while this study did not use the terms critical realism the approach was similar to work carried out in this thesis.…”
Section: Rationale Methodologymentioning
confidence: 99%